GAMBARAN MOTIVASI IBU YANG MEMILIKI BAYI USIA0-6 BULAN TENTANG PEMBERIAN ASI EKSKLUSIF DI WILAYAH POLINDES DESA SRIGADING KECAMATAN NGORO â MOJOKERTO - Khalimatus SaÃ¢Â€Â™diya, Lida; Kusharyati (Jurnal Keperawatan Bina Sehat, 2014)
Breast milkis thefirst food, the mainand bestfor thebabythat is naturalbecause milkcontains a variety ofnutrientsis needed inthe process of growthanddevelopment of the baby, there are still manyamongmothers withinfantsnotexclusively breastfedinfants. This studyaims to determine themotivation ofmotherswhohad apictureof infants aged0-6 monthsofexclusive breastfeeding. The study designuseda descriptivesurvey, the population of allmotherswhohaveinfants aged0-6 monthsinthe DistrictNgoropolindesSrigadingVillageof Mojokertoregencyusingtotalsampling, data collectionbyquestionnaireandif throughstagesof editing,coding, scoring andtabulating. Laterpersentationin the form oftabulationfrequency distribution. The conclusion ofthis studyislargelymotivatedmothers withinfants aged0-6 monthsofexclusive breastfeedingMidleas many.The results ofthis studymaybeadditionalinformationandknowledgeabout the benefits ofexclusive breastfeedingforthe babys motherthatmotivatedthe motherto breastfeedher babyfor0-6months.